Belinurus Bronn, 1839 (Chelicerata, Xiphosura) has priority over Bellinurus Pictet, 1846. (November 2021) - Lamsdell, James C.; Clapham, Matthew E.
Abstract : In the first half of the nineteenth century, a marked shift occurred in our understanding and treatment of the chelicerate fossil record, with the differentiation and recognition of entirely extinct genera for the first time. At the heart of this taxonomic revolution were the Eurypterida (sea scorpions) and Xiphosura (horseshoe crabs), although both groups were in fact considered crustaceans until Lankester's (1881) seminal comparative anatomical study of the extant xiphosuran Limulus Müller, 1785 and modern scorpions. The oldest available eurypterid genus is Eurypterus deKay, 1825; the oldest available fossil arachnid genus name is that of the scorpion Cyclophthalmus Corda, 1835. However, there has been considerable historical confusion over the oldest available fossil xiphosuran genus name, which has been recognized alternately as Belinurus König (with a publication date of either 1820 or 1851) or the synonymous Bellinurus Pictet, 1846. Most recent treatments (e.g., Selden and Siveter, 1987; Anderson and Selden, 1997; Anderson et al., 1997; Lamsdell, 2016, 2021; Bicknell and Pates, 2020) have favored Bellinurus Pictet, 1846 as the available name; however, Haug and Haug (2020) recently argued that Belinurus König, 1820 is valid and has priority, a position then followed by Lamsdell (2020), prompting a reinvestigation of the taxonomic history of the genus. Upon review, it is clear that neither of the previously recognized authorities for Belinurus are accurate and that the two candidate type species for each genus are, in fact, synonyms. Given the convoluted and at times almost illogical history of the competing names, along with the most recent controversy as to which has priority, we present a complete history of the treatment of the genus to resolve the issue.